Individual differences in arithmetic: Implications for psychology, neuroscience and education - Dowker, A (Psychology Press Taylor and Francis Group, 2005)
Standards in numeracy are a constant concern to educational policy-makers. However, why are differences in arithmetical performance so marked? In Individual Differences in Arithmetic, Ann Dowker seeks to provide a better understanding of why these differences in ability exist, encouraging a more informed approach to tackling numeracy difficulties. This book reviews existing research by the author and by others on the subject of arithmetical ability and presents strong evidence to support a componential view of arithmetic. Focusing primarily on children, but including discussion of arithmetical cognition in healthy adults and neuropsychological patients, each of the central components of arithmetic is covered. Within this volume, findings from developmental, educational, cognitive and neuropsychological studies are integrated in a unique approach. This book covers subjects such as: • Counting and the importance of individual differences. • Arithmetic facts, procedures and different forms of memory. • Causes of, and interventions with, mathematical difficulties. • The effects of culture, language and experience. The educational implications of these findings are discussed in detail, revealing original insights that will be of great interest to those studying or researching in the areas of education, neuroscience and developmental and cognitive psychology. © 2005 Psychology Press.